2014
DOI: 10.1007/s11581-014-1153-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of low viscous ionic liquids: the dependence of the viscosity on the mass of the ions

Abstract: Straightforward syntheses of selected nondeuterated, partially deuterated, and fully deuterated room temperature ionic liquids (ILs) with the anions tris(pentafluoroethyl)trifluorophosphate, tetracyanoborate, and methyl sulfate were developed. The viscosity and the density of these ionic liquids were measured at various temperatures. The dissociation rate of the ionic liquid, the sizes of the cation and the anion, and the nature of the inter-ionic interaction are not influenced by deuteration, but viscosity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 15 publications
3
36
0
2
Order By: Relevance
“…Presumably, the low viscosity of the ILs with the borate anions [BH n (CN) 4− n ] − or [BF n (CN) 4− n ] − ( n= 1–2) compared to ILs with [B X 4 ] − ( X =CN, F) relates to less symmetrical mixed‐substituted anions. The low molecular mass of the cyanohydridoborate‐ILs compared to the respective cyanofluoroborate‐ILs is most likely the reason for their exceptional low viscosity. This is further confirmed by even higher viscosities of the chlorocyanoborate‐ILs [EMIm][BCl n (CN) 4− n ] compared to [EMIm][BF n (CN) 4− n ].…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Presumably, the low viscosity of the ILs with the borate anions [BH n (CN) 4− n ] − or [BF n (CN) 4− n ] − ( n= 1–2) compared to ILs with [B X 4 ] − ( X =CN, F) relates to less symmetrical mixed‐substituted anions. The low molecular mass of the cyanohydridoborate‐ILs compared to the respective cyanofluoroborate‐ILs is most likely the reason for their exceptional low viscosity. This is further confirmed by even higher viscosities of the chlorocyanoborate‐ILs [EMIm][BCl n (CN) 4− n ] compared to [EMIm][BF n (CN) 4− n ].…”
Section: Resultsmentioning
confidence: 57%
“…relates to less symmetrical mixed-substituted anions. The low molecular mass [37] of the cyanohydridoborate-ILsc ompared to the respective cyanofluoroborate-ILs is most likely the reason for their exceptional low viscosity.T his is further confirmed by even higherv iscosities of the chlorocyanoborate-ILs [EMIm] [BCl n (CN) 4Àn ] [40]…”
Section: Viscosities and Densities Of The Ilsmentioning
confidence: 99%
“…The difference between the trifluoromethylborate and the related pentafluoroethylborate is small, in general, but it increases with an increasing number of cyano groups (Figure ). The higher viscosities for anions with longer perfluoroalkyl chains may be explained by stronger van der Waals interactions and the higher mass of the anions . The exception discussed for [EMIm] 1 a and [EMIm] 2 a reflects the strong gain in charge delocalisation of a C 2 F 5 versus a CF 3 group.…”
Section: Viscosities Self‐diffusivities and Conductivities Of The Emmentioning
confidence: 99%
“…[17][18][19][20] In particular, and concerning the use of specific functional groups, Niedermeyer et al 21 focused on the effect of introducing a siloxane group in the imidazolium cation on the viscosity. It was found that in spite of the increment in the cation´s mass, the viscosity of [(SiOSi)C 1 Within the context of IL-based membranes for CO 2 separation, and despite the large array of different SILM systems developed during the last decade, 6,7,23 the gas permeation properties of SILMs with siloxane-functionalized cations have still not been entirely studied and discussed.…”
Section: Introductionmentioning
confidence: 99%